The Multicenter Pediatric and Adult Congenital EP Quality (MAP‐IT) Initiative—Rationale and Design: Report from the Pediatric and Congenital Electrophysiology Society's MAP‐IT Taskforce. (13th May 2013) - Seslar, Stephen P.; Kugler, John; Batra, Anjan S.; Collins, Kathryn K.; Crosson, Jane; Dubin, Anne M.; Etheridge, Susan; Kanter, Ronald; Papez, Andrew; Radbill, Andrew E.; Serwer, Gerald A.; Tanel, Ronn E.; et al.
Abstract: Multicenter clinical registries are increasingly recognized as valuable tools for establishing benchmarks, facilitating patient‐centered quality improvement and research. In 2010, the Pediatric and Congenital Electrophysiology Society convened a taskforce of its members to design, construct, and implement a clinical registry known as theM ulticenter Pediatric andA dult Congenital EP Qualit y (MAP‐IT) Initiative. The present aim of the MAP‐IT Initiative is to create an infrastructure by which we can measurably improve patient‐centered outcomes and reduce complications associated with electrophysiology studies and catheter ablation in pediatric and congenital heart disease patients. The purpose of this writing is to report the progress to date from three of the four subcommittees of the MAP‐IT taskforce. Specifically, we present our initial set of key data elements and definitions, recommended database table structure, and considerations regarding wide‐scale implementation of the registry. Development of a risk/complexity score for use in the MAP‐IT registry is presented in a separate companion manuscript. It is our intent that these manuscripts will serve to introduce the electrophysiology and pediatric cardiology community to the MAP‐IT initiative and provide a rationale for its design and recommended implementation strategy.